AB1194 Treatment of Rheumatoid Arthritis with Biological Dmards in China: A Multi-Center Cross-Sectional Study. (9th June 2015) - An, Y.; Liu, T.; Li, Z.; He, D.; Wu, L.; Li, J.; Liu, Y.; Bi, L.; Zhou, B.; Lin, C.; He, L.; Liu, X.; et al.
Abstract : Background: Biological disease modifying antirheumatic drugs (bDMARDs) have been increasingly prescribed for RA in mainland China. Large scale epidemiological studies are needed to understand the treatment patterns and experience of bDMARD therapy in China. Objectives: To characterize bDMARD therapy in Chinese RA patients in routine clinical practice. Methods: Fifteen Chinese hospitals participated in this multi-center cross-sectional observational study. Consenting patients aged ≥18 years diagnosed with RA and receiving marketed bDMARDs were included. Results: In total, 802 patients (81.3% women) met the inclusion criteria. The mean age (SD) was 49.0 (13.9) years. Analysis of available data of dosage and treatment duration of bDMARDs for all patients revealed that 66.6% patients were receiving ETN at a mean (SD) weekly dose of 38.2 (15.6) mg for 25.5 (47.0) weeks. The second most common bDMARD was tocilizumab administered to 17.0% patients at a mean weekly dose of 94.5 (21.9) mg for 4.7 (7.5) weeks. Only 7.5% and 6.6% patients were receiving adalimumab and infliximab, respectively. Using DAS28 score as the evaluation index, 32.8%, 42.2%, 12.4%, and 12.6% patients showed high, medium, low disease activity, and disease remission, respectively. Compared with patients (62.7%) receiving bDMARDs for <3 months, whose DAS28 score was 4.6 (1.5), those receiving bDMARDs for ≥3 months exhibited significantly lower DAS28 scores ( P <0.0001). In particular, patients (14.6%) receiving bDMARDs for ≥12 months exhibited DAS28 scores of 3.2 (1.4). In total, 89.5% patients were receiving a combination of bDMARDs and cDMARDs whereas 10.5% patients were receiving bDMARD monotherapy. Among the 84 patients receiving bDMARD monotherapy, 75.0%, 10.7%, 9.5%, and 4.8% were receiving etanercept (ETN), infliximab, tocilizumab, and adalimumab respectively; for ETN, 8.3% and 66.7% patients were using original ETN (Enbrel®) and ETN biosimilar (Yi Sai Pu®), respectively. Patients receiving concomitant therapy exhibited significantly lower DAS28 than patients receiving bDMARD monotherapy (4.3 vs. 4.8, P =0.011). Reasons for discontinuing or switching bDMARDs varied. For patients (n=58) who had received the same bDMARDs previously, the main reasons for discontinuing the bDMARDs were improvement of disease condition (31%), financial burden (24.1%), and adverse reactions (13.8%). For patients (n=93) switching to different bDMARDs, the main reasons were unsatisfactory efficacy of the previous bDMARDs (58.1%), adverse reactions (14.0%), improvement of disease condition (10.8%), and financial burden (10.8%). Conclusions: This is the first large scale multi-center study to characterize bDMARD therapy in China. Patients receiving bDMARDs ≥3 months showed significantly lower DAS28 scores than patients receiving bDMARDs <3 months, although the treatment target was not achieved within 12 months in routine practice. Currently, ETN and tocilizumab are the most commonly used bDMARDs in China, and the proportion of patients receiving bDMARD monotherapy is lower than that in European countries. These results suggest that bDMARD therapy in China can be improved in many aspects. Acknowledgements: This study was sponsored by Shanghai Roche Pharmaceuticals Limited Disclosure of Interest: None declared